2017
DOI: 10.1111/jfpp.13514
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to extend the shelf life of cottage cheese curds using food grade CO2‐α‐cyclodextrin complex powder: A preliminary study

Abstract: The use of CO2‐α‐cyclodextrin complex powder to hinder mold and yeast growth in cottage cheese was investigated. The powder was directly mixed into the curds before packaging to achieve different CO2 concentrations (300, 600, and 900 ppm, mg CO2/kg curd), followed by storing the samples at 7 and 25 °C for up to 6 weeks. The sample containers were opened to expose them to air for 15–20 min every week. The results showed the mold and yeast growth was significantly inhibited without affecting pH and moisture cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recently, Ho et al. (2018) reported that mixing CO 2 –α‐CD inclusion complex with cottage cheese curds extended their shelf life for up to 6 weeks. CO 2 was released slowly from the complex, solubilized into the curds, and diffused in the container headspace, inhibiting mold and yeast growth.…”
Section: Controlled Release Of Gases/volatiles For Active Food Packaging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ho et al. (2018) reported that mixing CO 2 –α‐CD inclusion complex with cottage cheese curds extended their shelf life for up to 6 weeks. CO 2 was released slowly from the complex, solubilized into the curds, and diffused in the container headspace, inhibiting mold and yeast growth.…”
Section: Controlled Release Of Gases/volatiles For Active Food Packaging Applicationsmentioning
confidence: 99%
“…Although the encapsulation of CO 2 into α-CD was patented in 1987 (Trotta et al, 2011), no commercial applications were found based on this technology, which could be attributed to the limited storage capacity achieved. Recently, Ho et al (2018) reported that mixing CO 2 -α-CD inclusion complex with cottage cheese curds extended their shelf life for up to 6 weeks. CO 2 was released slowly from the complex, solubilized into the curds, and diffused in the container headspace, inhibiting mold and yeast growth.…”
Section: Controlled Release Of Gases/volatiles For Active Food Packag...mentioning
confidence: 99%
“…According to Cramer only 1 was able to form crystals, while larger cyclodextrins such as 2 and 3 and did not. Recently the solid complex of CO 2 and 1 have been studied as a food product additive [ 9 11 ]. Anions of 1 in DMSO have been found to have a high capacity for capturing of CO 2 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%